Das Geschlecht der Inklusion - Budde, Jürgen; Offen, Susanne; Tervooren, Anja (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2016)
The volume shows how the expertise of women's and gender studies can enrich the debate on inclusion, and analyses how debates on inclusion and gender are interwoven. How can a claim to participation based on a broad understanding of inclusion be spelled out in terms of gender theory? What perspectives do women's and gender studies offer on the problems of exclusion processes in the medium of democratic promises of inclusion? How are the categories of gender and disability intertwined? How can a critical position on the programmatic debate on inclusion be formulated? The 12th Yearbook presents empirical and theoretical contributions to the relationship between approaches to inclusion and gender theory.